2016
DOI: 10.19082/2168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-ionizing electromagnetic field on the alteration of ovarian follicles in rats

Abstract: IntroductionIn recent years, there has been an increase in the attention paid to safety effects, environmental and society’s health, extremely low frequency electromagnetic fields (ELF-EMF), and radio frequency electromagnetic fields (RF-EMF). The aim of this research was to determine the effect of EMF on the alteration of ovarian follicles.MethodsIn this experimental study at Tabriz Medical University in 2015, we did EMF exposures and assessed the alteration of rats’ ovarian follicles. Thirty three-month old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…It may also decrease ovarian reserve, which can lead to infertility. [18][19][20][21][22][23] In modern societies, humans are inevitably submerged in a sea of various spectrums of electromagnetic fields. The adverse effects of exposure to electromagnetic fields on human depend on the density of the field and the duration of the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It may also decrease ovarian reserve, which can lead to infertility. [18][19][20][21][22][23] In modern societies, humans are inevitably submerged in a sea of various spectrums of electromagnetic fields. The adverse effects of exposure to electromagnetic fields on human depend on the density of the field and the duration of the exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Ранее в эксперименте с ежедневным 4-часовым облучением мышей ПеМП 50 Гц 3 мТ в течение периода гестации в потомстве у самок мышей наблюдали признаки нарушения фолликулогенеза с уменьшением количества примордиальных фолликулов и увеличением числа атретических фолликулов, при этом в фолликулах выявлены признаки апоптоза [30]. В другом исследовании также установлен негативный эффект длительного воздействия ПеМП 50 Гц на яичники крыс в период эмбрионального развития [8]. В проведенном нами исследовании также наблюдалось некоторое снижение числа примордиальных и первичных фолликулов с увеличением количества антральных фолликулов; это свидетельствует о том, что во взрослом организме на фоне длительного предшествующего воздействия ПеМП КНЧ возможны изменения в процессах созревания фолликулов.…”
Section: Morphological Structure Of Ovaries and Uterus In Rats From Gunclassified
“…Известно, что любые экзогенные физические и химические факторы, способные прямо или опосредованно влиять на формирование и функционирование клеток, органов и системы в целом на разных этапах онтогенеза, могут привести к нарушениям эмбрионального развития органов, появлению заболеваний и, как следствие, снижению репродуктивной функции [1,5]. Так, ранее в экспериментах на крысах и мышах показаны неблагоприятные результаты длительного воздействия ПеМП КНЧ на репродуктивную систему самцов и самок, при этом выявлены изменения веса репродуктивных органов, содержания половых гормонов, нарушения эстрального цикла и овогенеза у самок и сперматогенеза у самцов [5,[8][9][10]. Но одновременно в ряде исследований отмечено отсутствие каких-либо значимых неблагоприятных эффектов при воздействии ПеМП КНЧ на репродуктивную систему человека и животных [11,12].…”
unclassified
“…h The difference between Group 2 and Group 4 was statistically significant (P = 0.018). of oocyte nuclei, decreased numbers of ovarian follicles, and DNA damage (1,2,25,26). In our study, we similarly found significant degeneration in mature follicles in the group exposed to radiation.…”
Section: Groupmentioning
confidence: 99%
“…As a consequence of technological improvements, exposure to magnetic fields has been increasing. The harmful effects of chronic exposure to magnetic fields can be observed in all tissues of the human body, particularly in the ovaries (1,2).…”
Section: Introductionmentioning
confidence: 99%